Quantifying Quality of Life Incorporating Daily Life into Medicine - Wac, Katarzyna; Wulfovich, Sharon; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book presents the rise of technology-enabled methods and tools for objective, quantitative assessment of Quality of Life (QoL), while following the WHOQOL model. It is an in-depth resource describing and examining state-of-the-art, minimally obtrusive, ubiquitous technologies. Highlighting the required factors for adoption and scaling of technology-enabled methods and tools for QoL assessment, it also describes how these technologies can be leveraged for behavior change, disease prevention, health management and long-term QoL enhancement in populations at large. Quantifying Quality of Life: Incorporating Daily Life into Medicine fills a gap in the field of QoL by providing assessment methods, techniques and tools. These assessments differ from the current methods that are now mostly infrequent, subjective, qualitative, memory-based, context-poor and sparse. Therefore, it is an ideal resource for physicians, physicians in training, software and hardware developers, computer scientists, data scientists, behavioural scientists, entrepreneurs, healthcare leaders and administrators who are seeking an up-to-date resource on this subject.
Introduction to Quality of Life and WHOQOL model -- Physical health: Activities of daily living -- Physical health: Dependence on medicinal substances and medical -- Physical health: Energy and Fatigue -- Physical health: Mobility -- Physical health: pain and discomfort -- Physical health: sleep and rest -- Physical health: work capacity -- Psychological: bodily image and appearance -- Psychological: negative and positive feelings -- Psychological: self-esteem -- Psychological: spirituality/religion/personal beliefs -- Psychological: thinking, learning, memory and concentration -- Social relationships: personal relationships +social support -- Social relationships: sexual activity -- Environment: financial resources -- Environment: freedom, physical safety and security -- Environment: health and social care: accessibility and quality -- Environment: home environment -- Environment: opportunities for acquiring new information and skills -- Environment: participation in and opportunities for recreation/leisure activities -- Environment: physical environment (pollution, noise, traffic, climate) -- Environment: Transport -- Future directions. .
Keywords: Medical informatics; Quality of life; Bioinformatics; Health Informatics; Quality of Life Research; Bioinformatics; Computational and Systems Biology